Platform Studies: The Rules of Engagement - Burgess, Jean; Baym, Nancy; Cunningham, Stuart; Craig, David; Helmond, Anne; Bucher, Taina; John, Nicholas; Nissenbaum, Asaf (AoIR Selected Papers of Internet Research, 2016)
Social media platforms like Twitter, Facebook and YouTube are central to people’s experiences of the internet and mobile media, and increasingly extend far beyond communication or entertainment, into transport, health, and finance. These platforms also serve up and serve as data for internet scholars and practitioners. How should we best approach platforms as objects of study? How do platforms’ rules and norms for engagement shape the practices we study? How do the material rules of these systems – their algorithms, their APIs, the analytics they provide – shape what we can know about them?While the importance of and methods for studying platforms have long been debated in game studies (Bogost & Montfort, 2009; Apperley & Parikka, 2015), this panel represents a second wave of platform studies, one that focuses on thinking critically about the best ways to understand the roles platforms play in mediating our media, communication and cultural environments; and one that integrates materialist approaches such as software studies with the core concerns of the media and communication disciplines understood more broadly. We bring together four papers that examine, first, how platforms shape what can be known about them; and second, to what extent we can understand them not only despite but through those processes and the traces they leave behind.Each paper models a distinctive theoretical and/or methodological approach; and they collectively engage with and across diverse media cultures, paying specific attention to the sociotechnical arrangements that coordinate and influence them.1. How affordances arise through relations between platforms, their different types of users, and what they do to the technology;2. How the social media APIs that scholars so often use for research are—for commercial reasons—skewed positively toward ‘connection’ and thus make it difficult to understand practices of ‘disconnection’;3. A biography of Twitter (a story told through the intertwined stories of its key features and the social norms that give them meaning, drawing on archival material and oral history interviews with users); and4. Insights into the actual uses to which audience data analytics are put by content creators in the new screen ecology (and the limitations of these analytics).*References*Apperley, T., & Parikka, J. (2015). Platform Studies’ Epistemic Threshold.Games and Culture, doi:1555412015616509.Bogost, Ian and Nick Montfort. 2009. ‘Platform Studies: Frequently Questioned Answers.’ In Proceedings of the Digital Arts and Culture Conference. http://escholarship.org/uc/item/01r0k9br.pdf.